2016
DOI: 10.1007/s10570-016-0964-4
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of cellulose nano-crystals through a sequential process of cellulase pretreatment and acid hydrolysis

Abstract: In this paper, a cellulase pretreatment was studied prior to the acid hydrolysis to decrease the total acid usage during the cellulose nano-crystals (CNC) preparation from a bleached softwood kraft pulp. Cellulase pretreatment facilitates the subsequent acid hydrolysis to produce CNC with similar quality to that of the control, but at a lower sulfuric acid concentration. The underline mechanism is that cellulase pretreatment led to the formation of more carbonyl groups which can be oxidized into carboxyl group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…4a. As can be seen, CNC showed uniform needle-like shape with 250-nm length and 12-nm diameter, which was similar with the reported works (dos Santos et al 2013;Rhim et al 2015;An et al 2016). From Fig.…”
Section: Extraction Of Cellulose Nanocrystalsupporting
confidence: 91%
“…4a. As can be seen, CNC showed uniform needle-like shape with 250-nm length and 12-nm diameter, which was similar with the reported works (dos Santos et al 2013;Rhim et al 2015;An et al 2016). From Fig.…”
Section: Extraction Of Cellulose Nanocrystalsupporting
confidence: 91%
“…These results could be attributed to the presence of sulfonic acid ester groups on increasing CNF surfaces. [ 13,36 ] Surface roughness of CNF layers confirmed the size change of CNFs (Figure S2, Supporting Information). The AFM scans directly revealed the haystack morphology of the randomly packed CNFs (Figure 2b).…”
Section: Resultsmentioning
confidence: 69%
“…In the work described in this paper, a two-stage treatment process combining enzymatic treatment and mechanical refining was investigated to improve the oxidation efficiency of bleached bamboo kraft pulp during TEMPO-mediated oxidation and facilitate the production of NFC. Based on previous literature, 26,33 we hypothesized that the combination of cellulase treatment and mechanical refining can increase the fibre surface area, improve the accessibility of cellulose, and break down cellulose hydrogen bonds, thereby improving the TEMPO-mediated oxidation of cellulose and reducing energy consumption during the HPH process. Our results indicated that the utilization of a two-stage cellulase/mechanical refining treatment significantly facilitated the NFC production process, and improved the yield and decreased the fibril diameter of the resultant NFC.…”
Section: Introductionmentioning
confidence: 99%